Assessment of some genetic attributes in wheat (Triticum aestivum L.) using gene-specific molecular markers - Mahmud, Rona; Kabir, Muhammed Rezwan; Hoque, Md Ekramul; Akhond, Md Abdullah Yousuf (Agriculture and Natural Resources, 2018)
Twenty-four wheat genotypes were characterized for the presence of three stress related genetic attributes using gene-specific molecular markers. Polymerase chain reaction (PCR) products of approximately 110 bp of 1RS rye chromosome fragment from 16 genotypes were obtained using specific primer pairs indicating the presence of translocation in these lines. The same genotypes were screened for the presence of dwarfing genes where 19 genotypes showed the presence of either the Rht-B1b or Rht-D1b allele having a semi-dwarf phenotype. Two of the genotypes (Kheri and Sufi) had wild type alleles in both the loci and two other genotypes showed the presence of double dwarf alleles (Rht-B1b + Rht-D1b). A 16.9 kDa HSP gene was characterized by validating a single-nucleotide polymorphism (SNP) linked with thermo tolerance in wheat. Thirteen of the 24 genotypes, which failed to amplify the specific PCR product due to the presence of an SNP, are expected to show tolerance for heat stress. Among the genotypes, Sonora-64, Balaka, Barkat, Aghrani and BARI Gom-24 (Prodip) tested positive for all the three markers evaluated (rye translocation, dwarfing genes and heat tolerance). These genotypes could be used to improve various stress tolerance attributes in wheat for future breeding programs.